Determination the Research Priorities in the Field of HIV/AIDS in Iran: A Systematic Review Article - Amin DOOSTI-IRANI; Kourosh HOLAKOUIE-NAIENI (Tehran University of Medical Sciences, 2016)
Background: HIV and AIDS have many different epidemiological, social and political aspects. The aim of this study was to determine the research priorities according to the necessary aspects of HIV and AIDS in Iran. Methods: The national and international databases were searched to obtain the published articles regarding HIV and AIDS in Iran. All Epidemiologic studies were included in this review for assess research priorities. Results: Of 3059 retrieved references, 362 studies were included. The most studies were conducted in Tehran, Kermanshah, Fars and Kerman provinces. The cross-sectional studies with 71.55% have higher proportion. Studies related to adherence to treatment (0.55%), drug resistance (0.83%) and experience, perception and behavior of HIV/AIDS patients (0.83%) had the lowest proportion of conducted studies. Proportion of studies regarding prevention of HIV was 2.76%. The authors of studies on female sex workers (FSWs) (63.64%) and prisoners (58.82%) suggested further studies on these groups. Conclusion: According to our results, the high-risk groups such as female sex workers, injecting drug users and prisoners are in priority for research. Moreover, topics related to the prevention of HIV and AIDS, adherence to treatment and antiretroviral drug resistance are other research priorities in Iran.